Critical heat flux enhancement in saturated pool boiling using water-based nanofluid with honeycomb porous plate - Mt Aznam, Suazlan; Shoji, Mori; Ryuta, Yanagisawa; Kunito, Okuyama (American Society of Mechanical Engineers (ASME), 2015)
The critical heat flux (CHF) limit is a great concern by many in the field of heat removal technology through pool boiling system. External cooling of pressure reactor vessel by in-vessel retention (IVR) method will involve boiling process in order to remove decay heat from the molten core through the lower head of the vessel. Increasing CHF could give extra safety margin for nuclear power plant to operate. Many researchers have shown that CHF is significantly enhanced by nanofluids compared to pure water. Nanoparticle deposited on heated surface improves surface wettability in which sustain more liquid to heat transfer surface. Therefore, dry out regions is delayed and further CHF enhancement is observed. On the other hand, surface modification by attaching honeycomb porous plate on heated surface have shown CHF enhancement approximately twice in comparison with plain surface. This is due to automatic liquid supply by capillary action and separation of liquid and vapor path contributed by the honeycomb structure. In the present study, the effects of surface modification by water-based nanofluid concentrations and honeycomb porous plate were investigated experimentally in saturated pool boiling atatmospheric pressure. Experimental result for combination of honeycomb porous plate and water-based nanofluids concentration of 4.0 g/L (0.110% by volume) shows the most enhanced CHF compared to other surface modification.